FAKTOR-FAKTOR YANG MEMENGARUHI PENGHINDARAN PAJAK PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - DIYANIVENA DEBORA; EDDY JONI (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study is to examine dan determine the effect of firm size, return on asset, leverage, capital intensity, sales growth, composition of independent commissioners, firm age dan audit committee on tax avoidance. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2020. This study used a purposive sampling method in sampling. From the total population, 56 companies are produced so that are 224 data used as research samples. The data in this study were processed using IBM SPSS Statistics 24. This study used multiple regression analysis model to examine the relationship between the independent variables dan the dependent variable. The research resources are taken from Indonesia Stock Exchange website. The results of this study indicate that return on assets dan sales growth have influence to tax avoidance, while firm size, leverage, capital intensity, composition of indenpendent commissioners, firm age dan audit committee have no influence on tax avoidance.